Seizures in 204 comatose children: incidence and outcome. - Kirkham, F; Wade, A; McElduff, F; Boyd, S; Tasker, R; Edwards, M; Neville, BG; Peshu, N; Newton, C (2012)
PURPOSE: Seizures are common in comatose children, but may be clinically subtle or only manifest on continuous electroencephalographic monitoring (cEEG); any association with outcome remains uncertain. METHODS: cEEG (one to three channels) was performed for a median 42 h (range 2-630 h) in 204 unventilated and ventilated children aged ≤15 years (18 neonates, 61 infants) in coma with different aetiologies. Outcome at 1 month was independently determined and dichotomized for survivors into favourable (normal or moderate neurological handicap) and unfavourable (severe handicap or vegetative state). RESULTS: Of the 204 patients, 110 had clinical seizures (CS) before cEEG commenced. During cEEG, 74 patients (36%, 95% confidence interval, 95% CI, 32-41%) had electroencephalographic seizures (ES), the majority without clinical accompaniment (non-convulsive seizures, NCS). CS occurred before NCS in 69 of the 204 patients; 5 ventilated with NCS had no CS observed. Death (93/204; 46%) was independently predicted by admission Paediatric Index of Mortality (PIM; adjusted odds ratio, aOR, 1.027, 95% CI 1.012-1.042; p < 0.0005), Adelaide coma score (aOR 0.813, 95% CI 0.700-0.943; p = 0.006), and EEG grade on admission (excess slow with >3% fast, aOR 5.43, 95% CI 1.90-15.6; excess slow with <3% fast, aOR 8.71, 95% CI 2.58-29.4; low amplitude, 10th centile <9 µV, aOR 3.78, 95% CI 1.23-11.7; and burst suppression, aOR 10.68, 95% CI 2.31-49.4) compared with normal cEEG, as well as absence of CS at any time (aOR 2.38, 95% CI 1.18-4.81). Unfavourable outcome (29/111 survivors; 26%) was independently predicted by the presence of ES (aOR 15.4, 95% CI 4.7-49.7) and PIM (aOR 1.036, 95% CI 1.013-1.059). CONCLUSION: Seizures are common in comatose children, and are associated with an unfavourable outcome in survivors. cEEG allows the detection of subtle CS and NCS and is a prognostic tool.